La musica nel secolo delle masse (Musica e società) (Nóema, 2011)
Muovendo dalle trasformazioni avvenute nella musica tra fine ‘800 e inizio ‘900, l’autore s’interroga sulle modalità con cui le “masse” hanno mutato gli assetti della vita economica, sociale e culturale. La riflessione prende spunto dal libro di Alex Ross Il resto è rumore. Ascoltando il XX secolo. The music during the century of the masses (Music and society)Focusing on the transformations that took place in the music between the late '800 and early '900, the author wonders about how the "masses" have changed the structure of economic, social and cultural life. The reflection is inspired by the book by Alex Ross The rest is noise. Listening to the Twentieth Century.
Keywords: musica; masse; music; masses; Alex Ross; The Rest Is Noise; Listening to the Twentieth Century; Richard Strauss; Salome; Mahler